PENGEMBANGAN MEDIA PEMBELAJARAN E-MODUL FLIPBOOK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SEKOLAH DASAR PADA MATERI KERAGAMAN BUDAYA - Rahae, Imelda Iin; Mahananingtyas, Elsinora; Johannes, Nathalia Y (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
This research aims to reduce boredom and improve critical thinking skills in the learning process. To reduce student boredom studying with printed modules. This type of research is development research using the ADDIE model to develop products. Data collection methods use questionnaire methods, learning outcomes tests, observations. Data analysis was carried out using qualitative analysis techniques and quantitative analysis techniques. The subjects of this research involved 12 fourth grade elementary school students. Media Validation based on 3 experts consisting of 2 lecturers and 1 social studies subject teacher with assessment results on 3 aspects, namely the material suitability aspect 4.16 categorized as valid, the material presentation aspect 4.33 categorized as very valid, the media design aspect 4.33 categorized very valid and limited field trials which concluded suggestions and improvements to learning media from students, and general field trials obtained a score of 4.32 which was categorized as very valid. Based on data analysis from the validation results obtained, it can be concluded that the Flippbook e-module learning media is suitable for use as a learning media for social studies learning content in grade IV elementary schools. The implication of this research is that the use of flippbook e-module learning media certainly has a positive impact on students and helps teachers in utilizing technology in designing IT-based learning media.